High entropy alloy (HEA) coatings for tribological applications - a review - S Sabarinath; Vighnesh Raj; Lakshmi V. Nair; Vinoy Thomas; Nasirudeen Ogunlakin; Viswanathan S. Saji (Results in Engineering, 2025)
High entropy alloy (HEA) coatings have garnered significant attention owing to their outstanding mechanical and tribological properties, as well as their resistance to high-temperature oxidation. These coatings consist of multiple principal elements, distributed in roughly equal atomic percentages. This characteristic makes them well-suited as coating materials for extreme operational conditions. This review delves into the realm of tribological thermal barrier coatings (TBCs), providing an account of fundamental principles and recent advancements in the context of HEA coatings. The review commences by elucidating the intricacies of substrates and coating parameters, detailing the properties of the substrate that influence coating performance. A focal point is then established on HEA coatings, with an overview of major processing techniques and a thorough examination of microstructural features and mechanical properties and how they influence friction and wear characteristics.